Work-related injuries as cause of hospitalization - Rafaela Scheid; Mathina Alice Gressler; Débora Martins; Luciana Simon Fanfa; Suzane Beatriz Frantz Krug (Universidade de Santa Cruz do Sul, 2012)
Rationale and Objectives: To identify possible cases of hospitalization due to work-related accidents and injuries, establishing the profile of patients admitted to a teaching hospital in southern Brazil between 2008 and 2010. Method: A descriptive, retrospective documental study, of which data were collected from 40 medical records of patients admitted between January 2008 and December 2010. After data collection we conducted a search of work-related cases from the Workers' Health Notification System (SIST). Results: Of the 40 reviewed records, only 1 (2.5%) contained a work-related accident record. In 45% of them, the information provided suggested an association between work and hospitalization. Among hospitalizations identified as work-related, 80% occurred with men and 89% of cases were discharged after improvement. One individual died and the outcome was not described in another record. Conclusion: The study showed the reality of not establishing a causal link between work and health problems of patients, resulting in the absence of investigation of work-related illnesses or accidents, which contributes to the panorama of injury underreporting. KEYWORDS: Workers' Health. Hospitalization. Labor.